การพัฒนารูปแบบการบริหารแบบมีส่วนร่วมสำหรับโรงเรียนดีประจำตำบล - เกสิณี ชิวปรีชา (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purpose of this research were to 1) study degree of success and importance for a participative management of outstanding subdistrict school. 2) develop a participative management model for outstanding subdistrict school. It was processed by a research and development approach. Which consisted of 4 steps as follows: (1) study of 123 schools (2) a construction of the model (3) a verification of the model by 30 expert and an evaluation of the model by focus group 15 expert and the final improvement of the model. The research instruments were a questionnaire and an evaluation from. Data were analyzed by content analysis and descriptive statistics. The research results were as follow: 1)The model composed of 4 parts. The 1st part was a participative management model for outstanding subdistrict school is professional and community control. The 2nd part wasthe principle and objective of a participative management model. The 3rd part was an Implementation process which consisted of 4 factors. They were preparation, implementation process, evaluation and report. And the 4th part was conditions of a the participative management model which composed of successful and obstacle factors and there sources of factors (superordinate, subordinate and participants). 2) The developed model was evaluated at a high level by experts and school administrators to be suitable and possible for implementation.